UNJUKKERJA SISTEM LTSP SERVER BERDASAR VIRTUAL APPLIANCE PADA WAN - , Prihadi Yogaswara; , Widyawan, S.T., M.Sc.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Althought newer Server Based Computing technology, that can be used to centralize desktop software maintenance continue to developed, such as Virtual Vesktop Infrastructure, Desktop as a Service, OS Streaming, Terminal Server still considered more experienced method. One of open source application can be use to build terminal server is LTSP. However, LTSP have an limitation when provide network booting, that can be helped by tunneling with ethernet bridging method using OpenVPN. Using that method, LTSP can be hosted in virtualserver, such as Infrastructure as a Service (IaaS). To simplifying LTSP server deployment, Virtual Appliance method can be used. However if LTSP server implemented on IaaS, separation between client and server location, bring consequences transfered data along medium experiencing degradation that cause by Round Trip Time (RTT) and Packet Loss Rate (PLR). From the observation when TCP and UDP used in tunneling connection, obtained UDP connection yield shorter time needed by network booting only when PLR value is 0. Unideal condition also affect response time on client Graphic User Interface(GUI). Experiment result UDP connection yield better performance not only when PLR value 0. Computation load experiment result unideal condition in network do not affect performance on client, while experiment on fat client result computation performance and GUI response time on client, not affected by network performance.